Modeling of the properties of the semiconductor solid solution Lu1-xVxNiSb in the presence of magnetic ordering - V.V. Romaka; V.A. Romaka; Yu. Stadnyk; L. Romaka; A. Horyn; V. Pashkevych; P. Haraniuk (Фізика і хімія твердого тіла, 2023)
Modeling of the thermodynamic, structural, energetic and magnetic properties of the semiconductor solid solution Lu1-xVxNiSb was carried out under the condition of the presence of a magnetic moment on the V atoms and the occurrence of spontaneous magnetization. It is shown that the change in the unit cell parameter a(x) and the mixing enthalpy ΔHmix(х) depends little on the presence or absence of spontaneous magnetization. Modeling of the distribution of the density of electronic states DOS in the presence of a magnetic moment on V atoms revealed the splitting of energy states with spins up and down while preserving the band gap εg of Lu1-xVxNiSb. The relationship between the concentration of magnetic V atoms in Lu1-xVxNiSb and the Curie temperature ТС, when spontaneous magnetization is destroyed and the substance becomes paramagnetic, is established. The solid solution semiconductor Lu1-xVxNiSb, provided spontaneous magnetization is present, can be considered as a promising magnetocaloric.